Laparoscopic pyeloplasty in neonates and infants is safe and efficient - Langreen, S.; Ludwikowski, B.; Dingemann, J.; Ure, B. M.; Hofmann, A. D.; Kuebler, J. F. (Frontiers in Pediatrics, 2024)
Introduction Dismembered laparoscopic pyeloplasty (LP) is a well-accepted treatment modality for ureteropelvic junction obstruction (UPJO) in children. However, its efficacy and safety in infants, particularly neonates, remain uncertain. To address this significant knowledge gap, we aimed to compare outcomes between a cohort of neonates and infants undergoing LP vs. open pyeloplasty (OP) at less than 6 months and 6 weeks of age. Material and methods We conducted a retrospective analysis of data from patients who underwent primary pyeloplasty at our institution between 2000 and 2022. Only patients aged 6 months or less at the time of surgery were included, excluding redo-procedures or conversions. Ethical approval was obtained, and data were assessed for redo-pyeloplasty and postoperative complications, classified according to the Clavien–Madadi classification. A standard postoperative assessment was performed 6 weeks postoperatively. This included an isotope scan and a routine ultrasound up to the year 2020. Results A total of 91 eligible patients were identified, of which 49 underwent LP and 42 underwent OP. Patients receiving LP had a median age of 11.4 (1–25.4) weeks, compared to 13.8 (0.5–25.9) weeks for those receiving OP (p > 0.31). Both groups in our main cohort had an age range of 0–6 months at the time of surgery. Nineteen patients were younger than 6 weeks at the time of surgery. The mean operating time was longer for LP (161 ± 43 min) than that for OP (109 ± 32 min, p < 0.001). However, the mean operating time was not longer in the patient group receiving LP at ≤6 weeks (145 ± 21.6) compared to that in our main cohort receiving LP. There was no significant difference in the length of stay between the groups. Four patients after LP required emergency nephrostomy compared to one patient after OP. The rate of revision pyeloplasty in our main cohort aged 0–6 months at surgery was 8% in the patient group receiving LP and 14% in the patient group receiving OP (not significant). Three revisions after LP were due to persistent UPJO, and one was due to stent migration. Only one patient requiring revision pyeloplasty was less than 6 weeks old. Conclusion To our knowledge, this is one of the largest collectives of laparoscopic pyeloplasty performed in infants, and it is the youngest cohort published to date. Based on our experience, LP in neonates and infants under 6 months appears to be as effective as open surgery.